Pendampingan Produksi dan Pemasaran Digital Usaha Roti Berbasis Learning Management System untuk Penguatan Legalitas Usaha di Desa Seddur, Pamekasan: Production and Digital Marketing Assistance for Bread Businesses Using a Learning Management System to Strengthen Business Legality in Seddur Village, Pamekasan - Samsul Arifin; Elmi Tri Yuliandari; Ma'ruf sya'ban (Jurnal Dedikasi Hukum, 2025)
This community service initiative aims to increase production and marketing capacity while strengthening the partners’ understanding of the importance of legal compliance for M.J. Home Made Bakery, a microenterprise managed by a group of homemakers in Sedur Village, Pamekasan. The partners’ main challenges stem from limited production equipment—which remains conventional—and suboptimal marketing strategies, particularly regarding building brand awareness and ensuring the legal compliance of their home-based food business. To address these challenges, the program was implemented through training on production enhancement using an automatic dough mixer, as well as the development of digital marketing strategies leveraging e-commerce and social media. The key innovation introduced was the implementation of the Kampung Roti Bu-Ibu Learning Management System (LMS Karbu), an online platform designed to support flexible and sustainable training processes. Implementation methods included outreach, training, technology adoption, mentoring, and evaluation. Program results demonstrate an increase in partner capacity in both production and marketing. On the production side, the procurement of automatic dough mixers and large-capacity ovens has proven to increase product quantity. Meanwhile, on the marketing side, training on the importance of brand awareness through the LMS Karbu platform has successfully improved participants’ understanding of strategies to build consumer trust through quality improvement and product diversification. Additionally, this initiative highlighted the urgency of strengthening business legality, particularly the acquisition of a Home Industry Food Production certificate, as the focus of future programs. Consequently, this initiative reinforces production, marketing, and legal awareness regarding home-based businesses. Abstrak Pengabdian masyarakat ini bertujuan untuk meningkatkan kapasitas produksi dan pemasaran sekaligus memperkuat pemahaman mitra terhadap pentingnya legalitas usah M.J Home Made Bakery, sebuah usaha mikro yang dikelola oleh kelompok ibu rumah tangga di Desa Sedur, Pamekasan. Permasalahan utama mitra terletak pada keterbatasan peralatan produksi yang masih konvensional dan strategi pemasaran yang belum optimal, khususnya dalam membangun kesadaran merek (brand awareness) dan legalitas usaha pangan rumah tangga. Untuk menjawab permasalahan tersebut, program dilaksanakan melalui pelatihan peningkatan produksi dengan penggunaan mesin pengaduk adonan roti otomatis, serta pengembangan pemasaran digital berbasis e-commerce dan media sosial. Inovasi utama yang dihadirkan adalah penerapan Learning Management System Kampung Roti Bu-Ibu (LMS Karbu), sebuah platform daring yang dirancang untuk mendukung proses pelatihan secara fleksibel dan berkelanjutan. Metode pelaksanaan mencakup sosialisasi, pelatihan, penerapan teknologi, pendampingan, dan evaluasi. Hasil program menunjukkan peningkatan kapasitas mitra baik dari aspek produksi maupun pemasaran. Dari sisi produksi, pengadaan mesin pengaduk adonan otomatis dan oven berkapasitas besar terbukti meningkatkan kuantitas produk. Sementara itu, dari sisi pemasaran, pelatihan tentang pentingnya brand awareness melalui platform LMS Karbu berhasil meningkatkan pemahaman peserta mengenai strategi membangun kepercayaan konsumen melalui peningkatan kualitas serta diversifikasi produk. Selain itu, kegiatan ini juga menguraikan pengantar urgensi penguatan legalitas usaha, khususnya kepemilikan sertifikat Produksi Pangan Industri Rumah Tangga sebagai fokus program selanjutnya. Oleh karena itu, kegiatan ini memperkuatproduksi, pemasaran, dan kesadaran hukum atas usaha rumah tangga.